Adult-onset Still’s disease during pregnancy: two case reports and a comprehensive literature review - Xu, Wenchao; Huang, Shuang; Li, Juanli; Li, Ting; Lu, Yu; Yang, Liu; Zhang, Jianyu; Li, Xue; Chen, Jian (Frontiers in Medicine, 2025)
BackgroundAdult-onset Still’s disease (AOSD) is a rare systemic inflammatory disorder marked by recurrent fever, rash, arthritis, and multi-organ involvement. Its occurrence with pregnancy complicates diagnosis and management.ObjectivesTo present the diagnosis and treatment process of two pregnant patients with newly diagnosed AOSD.CasesTwo cases of AOSD were initially diagnosed during pregnancy. Case one involved a pregnant woman at 16 + 2 weeks of gestation with recurrent fevers, rash, and myalgia. She responded well to treatment with methylprednisolone and cyclosporine and subsequently had a normal vaginal delivery. Case two involved a pregnant woman at 30 + 6 weeks of gestation who presented with systemic joint pain and fever. After being diagnosed with AOSD, she underwent a cesarean section. Treatment included methylprednisolone, cyclosporine, and addition of methotrexate postpartum.ConclusionAdult-onset Still’s disease can be triggered by pregnancy, requiring a multidisciplinary approach for optimal management and fetal outcomes.